Strategi Pengembangan Infrastruktur Permukiman Pulau Kecil, Sulawesi Selatan - A. Nada Zahirah; Shirly Wunas; Mimi Arifin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Management of housing and settlements to ensure the realization of livable and affordable housing in a healthy, safe, harmonious, organized, planned, integrated and sustainable environment. The principle of livability also applies to small island settlements. This study aims to explain the conditions, needs and strategies of settlement infrastructure on small islands. The data used came from 86 respondents who are residents who live in one of the small islands of South Sulawesi obtained through probability sampling. The method were a questionnaire and in-depth interviews. The analysis was carried out descriptively, spatially, comparatively and SWOT. The results showed 1) Adequate infrastructure is a road network. Inadequate infrastructure is drainage networks, clean water systems, waste systems, household feces systems. Infrastructure that is not yet available is the electricity network and telecommunications network. 2) The condition of settlement infrastructure is in quadrant II which shows the strategy used is an aggressive maintainance strategy, namely an internal consolidation strategy by making improvements to the weakness factor to maximize the utilization of opportunities. The strategic steps taken are the development of renewable energy to support the development of tourism, the application of WWTP as a minmal technology that is owned in domestic waste treatment and waste management through fostered groups.